Synaptonemal complex analysis of hybrid and purebred water buffaloes (Bubalus bubalis) - Dat, K.; Gillies, C.B.; Dollin, A.E.; Hilmp, M. (2004)
The morphology of the Synaptonemal complex (SC) in river (2n = 50) and swamp (2n = 48) water buffaloes and their hybrids, was studied by electron microscopic analysis. In 2n = 49 hybrids, F2 and backcrosses the formation and pairing behaviour of a trivalent at zygotene‐pachytene confirmed that river and swamp buffaloes differ by a centromere‐to‐telomere (C‐T) tandem fusion. While 29% of spermalocytes from a purebred river buffalo and 16% from a purebred swamp buffalo had pairing abnormalities, a significantly higher frequency of abnormalities (48 72%) was recorded in F1 F2, and backcrosses with 2n = 48, 49 or 50. Highest abnormality frequencies occurred in 2n = 49 bulls. Abnormal pairing configurations often resulted from interactions between unpaired chromosome axes or segments. Zygotene‐pachytene mciotic progress appeared delayed in hybrid bulls, and the frequency of SC abnormalities decreased from XY type I substage to type V substage. The variation in SC abnormality data from hybrids was consistent with the levels of sperm abnormality previously reported. Copyright © 1994, Wiley Blackwell. All rights reserved